A Randomized Prospective Double‐Blind Comparison Trial of Clomiphene Citrate and Anastrozole in Raising Testosterone in Hypogonadal Infertile Men. (14th July 2015) - Helo, Sevann; Ellen, Joseph; Mechlin, Clay; Feustel, Paul; Grossman, Michael; Ditkoff, Edward; McCullough, Andrew
Abstract Aim Clomiphene citrate (CC) and anastrozole (AZ) have been used off label to increase testosterone (T) in hypogonadal infertile men (HIM). Both medications have been shown to increase T with different effects on estradiol (E2) and T‐to‐E2 ratios. There are no reported randomized trials comparing CC and AZ to improve T levels in HIM. We aimed to establish equivalence of CC vs. AZ with respect to improvement in T levels in HIM. Methods We randomized 26 HIM (T less than 350 ng/dL and normal luteinizing hormone [LH]). Patients were randomized to CC (25 mg/day) or AZ (1 mg/day) for 12 weeks. Hormones assayed were total T, free T, E2, LH, follicle stimulating hormone (FSH), and sex hormone binding globulin (SHBG). Patient‐reported outcomes were the International Index of Erectile Function, Erection Hardness Scale, and the Androgen Deficiency in the Aging Male questionnaires. Blood tests and questionnaires were recorded at baseline, 6 and 12 weeks. Semen analyses were performed at baseline and 12 weeks. Results T increased significantly from baseline in both groups at 6 and 12 weeks. There was a significantly larger increase in T and mean increase from baseline in CC vs. AZ (571 vs. 408 ng/dL, respectively). Whereas E‐2 levels increased in the CC group, they decreased in the AZ group. Though both groups demonstrated an increase in T‐to‐E‐2 ratio from baseline, statistic significance at 6 and 12 weeks was only achieved with AZ. Neither group demonstrated significant changes in seminal parameters or patient‐reported outcomes. Conclusions We failed to demonstrate equivalence of CC vs. AZ. CC resulted in significantly higher T levels than AZ. AZ resulted in a significantly larger increase in T/E‐2 ratio than CC. No significant differences between CC and AZ on seminal parameters or patient‐reported outcomes were demonstrated. Helo S, Ellen J, Mechlin C, Feustel P, Grossman M, Ditkoff E, and McCullough A. A randomized prospective double‐blind comparison trial of clomiphene citrate and anastrozole in raising testosterone in hypogonadal infertile men. J Sex Med 2015;12:1761–1769.